2017
DOI: 10.1002/chem.201703742
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies on the Role of [CuII(CO3)n]2−2n as a Water Oxidation Catalyst: Carbonate as a Non‐Innocent Ligand

Abstract: Recently it was reported that copper bicarbonate/carbonate complexes are good electro-catalysts for water oxidation. However, the results did not enable a decision whether the active oxidant is a Cu or a Cu complex. Kinetic analysis of pulse radiolysis measurements coupled with DFT calculations point out that Cu (CO ) complexes are the active intermediates in the electrolysis of Cu (CO ) solution. The results enable the evaluation of E°[(Cu (CO ) ) ]≈1.42 V versus NHE at pH 8.4. This redox potential is in acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 81 publications
1
16
0
1
Order By: Relevance
“…In the water oxidation mechanism,t he intermediate formation of peroxides may involve the following steps [Equations (1)-(4))]. [45] In Equation (1), the mechanism involves water nucleophilic attack on the metal-oxo species. [46][47][48][49] Whereas in Equations (2)-(4), the involvement of radical pathways through the coupling interaction of two metallo-oxyl/hydroxylr adicals is proposed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the water oxidation mechanism,t he intermediate formation of peroxides may involve the following steps [Equations (1)-(4))]. [45] In Equation (1), the mechanism involves water nucleophilic attack on the metal-oxo species. [46][47][48][49] Whereas in Equations (2)-(4), the involvement of radical pathways through the coupling interaction of two metallo-oxyl/hydroxylr adicals is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…[70] Av ery recent study on an aluminium-porphyrin complexs howed the catalytic formation of peroxo-monocarbonate in the presence of bicarbonate/carbonate. [71] The role of carbonate in these processes is attributed mainly to two properties of carbonate: [72] a) it is as trong base and as trong s donor, therefore it stabilizes transition-metal complexes in high oxidation states; [15,45,70] b) its relativelyl ow oxidation potential [68,69] enhances electron transfer to the central cation. [45,70] Several mechanismsf or the role of carbonate in thesep rocesses can be proposed [Equations (5)-(8)]:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrary to the above proposal, Mizrahi et al concluded by combining pulse radiolysis experiments and detailed kinetic analysis with DFT calculations that the only plausible mechanism would be when C2O6 2 (formally CO4 2 + CO2) was produced as the first peroxide product from the decomposition reaction between two [Cu III (CO3)3] 3 complexes [23]. In the electrocatalytic process the electron transfer to the electrode was proposed to involve the oxidation of Cu II (CO3)n 2-2n to Cu III (CO3)n 3−2n directly without the involvement of CO3 • radical anions.…”
Section: Inorganic Ligandsmentioning
confidence: 89%
“…Meyerstein untersucht zurzeit den Mechanismus der Fenton‐Reaktion unter verschiedenen Bedingungen, die Rolle von Carbonat als Kokatalysator in katalytischen Oxidationsprozessen sowie Reaktionen von Radikalen mit Metallnanopartikeln in wässrigen Medien. Er verfasste einen Beitrag für das European Journal of Inorganic Chemistry über Nanopartikel in der katalytischen Reduktion von Perchlorat durch Radikale, und sein Bericht über Kupferbicarbonat/carbonat‐Komplexe als Wasseroxidationskatalysatoren erschien auf dem Titelbild von Chemistry – A European Journal …”
Section: Ausgezeichnet …unclassified